2017
DOI: 10.1016/j.sapharm.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist experiences of providing needle and syringe programmes in Ireland

Abstract: Article HighlightsCommunity pharmacists can provide quality harm reduction support to drug users via needle and syringe programmes (NSP). There is a need for appropriate strategies to raise awareness and meet service user specific needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Some consumers indicated they would opt to purchase kits from the pharmacy while others saw some limitations which needed to be overcome first, specifically privacy and confidentiality. These types of concerns have been identified in these environments among other substance consumers [ 9 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some consumers indicated they would opt to purchase kits from the pharmacy while others saw some limitations which needed to be overcome first, specifically privacy and confidentiality. These types of concerns have been identified in these environments among other substance consumers [ 9 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, consumer attitudes to harm reduction service provision have been mixed [ 9 ], largely as a result of perceived systemic barriers for consumers which are often evident at sites of delivery [ 10 , 11 ]. McVeigh et al underscored the necessity for enhancing pharmacists' harm reduction training and implementing appropriate strategies to raise awareness of the needs of substance consumers, cater to the diverse needs of individuals who inject drugs, foster trusting relationships, and facilitate engagement within a confidential service setting [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Routine voluntary testing of drug users for HIV began in 1985 and over the first 2 years, 19% of those tested were diagnosed as being HIV positive. Needle and syringe provision was first provided in Ireland in 1989 in the former Eastern Health Board (EHB) AIDS Resource Centre in Dublin, in response to the heroin problem at the time [19]. Methadone services, mainly focused on detoxification, have been available since 1992 [20] and were initially restricted to the capital, Dublin [17].…”
Section: Methodsmentioning
confidence: 99%
“…Collaboration between health services and community pharmacists has delivered harm reduction programmes of consistent quality in Europe [20,25], such as opioid substitution [34], needle exchange [35] and smoking cessation [36]. Similarly, experience with vaccination services has shown that they increase the uptake of vaccines in the population and are valued by the public [37,38].…”
Section: Pharmaceutical Care Services In the Community Pharmacy Settingmentioning
confidence: 99%